(3jhGbjJ GdehGbjJs - (3YeQ Hf eMeO Hf CMeO Hf ESeGYjd, CHh MaU, fLe GdOjf GdfSaj,J (B537 (3g` s ((3CMeO Hf Ydi Hf eMeO Hf CMeO s)
(3ChdgG (B:s
(3Chd GdehLhO Hg bhdg SFd QShd Gddg Ydjg GdSdGe Ch ai QeVGf djdI HQ gi ZjQ djdI GdbOQ bGd fYe djdI SHY YTQI hJSY YTQI hGMOi hYTQhf (B) s
(3BNQgG (B:s
(3hbO JeJ HGedGFi Ydjce jhGbjJ GdehGbjJ GdMSGf HGdGSJGP GdUMjM ef GdeTGjN JKGH cdge Ggd GdHjGf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B306 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B783s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2054s
Keywords: (3GdMOjK h GdeUWdMs